El nuevo constitucionalismo y las bases Del orden jurídico - Cassagne, Juan Carlos (Pontificia Universidad Católica del Perú, 2016)
Inside the field of Law, the usual question about the meaning of a determined concept or the question towards what it makes reference to has alwaysbeen complicated. In the last years, different events have produced that philosophical trends reconsider the understanding of the legal system.In the present article, the author does a presentation of what new constitutionalism means and its opinion towards it. The author also makes a critical analysis of the positivist and jusnaturalist visions, connecting them with the understandingof Law and the legal system, making an emphasis on Administrative Law.

En el campo del Derecho, la pregunta sobre qué significa o a qué hace referencia determinado concepto siempre ha sido complicada. En los últimos años diversos acontecimientos han ocasionado que corrientes filosóficas replanteen la forma de entender el orden jurídico.En el presente artículo, el autor hace una presentación de qué se entiende por nuevo constitucionalismo y su opinión sobre el mismo. Asimismo, realiza un análisis crítico de los planteamientos positivistas e iusnaturalistas, conectando los mismos con el entendimiento del Derecho y del orden jurídico, poniendo énfasis en la rama del Derecho Administrativo.
New constitutionalism and the foundations of the legal system
Keywords: Derecho; https://purl.org/pe-repo/ocde/ford#5.05.01